Zinc-doped Prussian blue enhances photothermal clearance of Staphylococcus aureus and promotes tissue repair in infected wounds - Li, Jun (Nat Commun, 2019)
The application of photothermal therapy to treat bacterial infections remains a challenge, as the high temperatures required for bacterial elimination can damage healthy tissues. Here, we develop an exogenous antibacterial agent consisting of zinc-doped Prussian blue (ZnPB) that kills methicillin-resistant Staphylococcus aureus in vitro and in a rat model of cutaneous wound infection. Local heat triggered by the photothermal effect accelerates the release and penetration of ions into the bacteria, resulting in alteration of intracellular metabolic pathways and bacterial killing without systemic toxicity. ZnPB treatment leads to the upregulation of genes involved in tissue remodeling, promotes collagen deposition and enhances wound repair. The efficient photothermal conversion of ZnPB allows the use of relatively few doses and low laser flux, making the platform a potential alternative to current antibiotic therapies against bacterial wound infections.